Sine, Cosine, and Polynomials
There is another way to solve this Laplace transform involving derivatives (which we will do in this post). I am also aware that we can decompose sin and cos into exponents using Eulier’s identity. I do this in the next post. However, I came up with this proof when I was 14 and before I had a good understanding of complex numbers. So, I wanted to showcase it.
One benefit of this proof is that I give a closed-form polynomial rather than an addition/subtraction of two polynomials. This form may be easier to use in certain applications.
Deriving a Recurrence
We want to evaluate L{tnsint} and L{tncost}. First, let’s do one iteration of integration by parts, starting with sine.
L{tnsint}=∫∞0tnsin(t)e−stdt(using integration by parts)=1sf(0)−1slimt→∞f(t)e−st+1s∫∞0f′(t)e−st dt=1s⋅0−1slimt→∞tnsin(t)e−st+1s∫∞0(ntn−1sin(t)+tncos(t))e−st dt=ns∫∞0tn−1sin(t)e−st dt+1s∫∞0tncos(t)e−st dt=nsL{tn−1sint}+1sL{tncost}The limit goes to 0 since the sint term is bounded between [−1,1], so it can be disregarded. Then, we just have the same limit as when we proved L{tn}. We now do similar with cosine.
L{tncost}=∫∞0tncos(t)e−stdt(using integration by parts)=1sf(0)−1slimt→∞f(t)e−st+1s∫∞0f′(t)e−st dt=1s⋅0−1slimt→∞tncos(t)e−st+1s∫∞0(ntn−1cos(t)−tnsin(t))e−st dt=ns∫∞0tn−1cos(t)e−st dt−1s∫∞0tnsin(t)e−st dt=nsL{tn−1cost}−1sL{tnsint}Now, we can combine these two facts and with a little bit of algebra get
L{tnsint}=ns2+1[s⋅L{tn−1sint}+L{tn−1cost}] L{tncost}=ns2+1[s⋅L{tn−1cost}−L{tn−1sint}]Proving a Closed-Form Formula
Now that we have L{tnsint} and L{tncost} in terms of each other, I am going to assert the following solution, which was derivated based on a series of substitutions and pattern matching.
L{tnsint}=n!(s2+1)n+1n+1∑k=0A(n−k)(n+1k)sk L{tncost}=n!(s2+1)n+1n+1∑k=0A(n−k+1)(n+1k)skThe function A(m) is defined as follows:
A(m)={1ifm≡0mod40ifm≡1mod4−1ifm≡2mod40ifm≡3mod4There are a few ways we can mathematically represent A(m) (which we will discuss at the end), but for now, we just need the interpretation of A(m). It gives an alternating series (positive/negative) for the even values of m, and disregards odd indices of m.
Now, I’ll prove my asserted equations by induction on n≥0. Using the base case of n=0, we get the following. Note that (10)=1, (11)=1, 0!=1, A(0)=1, and A(−1)=0.
(0)!(s2+1)11∑k=0A(−k)(1k)sk=1s2+1[A(0)(10)s0+A(−1)(11)s1]=1s2+1=L{sint} (0)!(s2+1)11∑k=0A(−k+1)(1k)sk=1s2+1[A(1)(10)s0+A(0)(11)s1]=ss2+1=L{cost}Now, to do the induction step, we use the result from above to evaluate L{tnsint}, assuming that the above equations hold for L{tn−1sint} and L{tn−1cost}
(s2+b2)n+1n!⋅L{tnsint}=(s2+b2)n(n−1)![s⋅L{tn−1sint} + L{tn−1cost}]=(s2+b2)n(n−1)!⋅(n−1)!(s2+b2)n[s⋅n∑k=0A(n−k−1)(nk)sk + n∑k=0A(n−k)(nk)sk]=n∑k=0A(n−k−1)(nk)sk+1 + n∑k=0A(n−k)(nk)skLet j=k+1 and reindex the first summation=n∑j=1A(n−j)(nj−1)sj + n∑k=0A(n−k)(nk)skNotice that adding a j=0 term to the first summation gives a 0 term since (n−1)=0Also, adding a k=n+1 term to the second summation will give a 0 term since A(−1)=0Finally, recall the identity (n+1k)=(nk)+(nk−1) thus, we combine the two summations=n+1∑k=0A(n−k)(n+1k)skWe do likewise for L{tncost}.
(s2+b2)n+1n!⋅L{tncost}=(s2+b2)n(n−1)![s⋅L{tn−1cost} − L{tn−1sint}]=(s2+b2)n(n−1)!⋅(n−1)!(s2+b2)n[s⋅n∑k=0A(n−k)(nk)sk − n∑k=0A(n−k−1)(nk)sk]=n∑k=0A(n−k)(nk)sk+1 − n∑k=0A(n−k−1)(nk)skLet j=k+1 and reindex the first summation=n∑j=1A(n−j+1)(nj−1)sj − n∑k=0A(n−k−1)(nk)skRecall the property that A(m)=−A(m+2) Thus, A(n−k−1)=−A(n−k+1)Now, it's the same argument as before to combine the summations=n+1∑k=0A(n−k+1)(n+1k)skScaling
To derive the scaled versions, we use the scaling property f(bt)=1bF(s/b).
L{tnsin(bt)}=1bnL{(bt)nsin(bt)}=1bn⋅1bn!((s/b)2+1)n+1n+1∑k=0A(n−k)(n+1k)(s/b)k=bn+1⋅n!(s2+b2)n+1n+1∑k=0A(n−k)(n+1k)(s/b)k=n!(s2+b2)n+1n+1∑k=0A(n−k)(n+1k)skbn−k+1Similarly
L{tncos(bt)}=1bnL{(bt)ncos(bt)}=1bn⋅1bn!((s/b)2+1)n+1n+1∑k=0A(n−k+1)(n+1k)(s/b)k=bn+1⋅n!(s2+b2)n+1n+1∑k=0A(n−k+1)(n+1k)(s/b)k=n!(s2+b2)n+1n+1∑k=0A(n−k+1)(n+1k)skbn−k+1Translation
Same as in the previous post, we can use the identities
sin(θ+ϕ)=sin(θ)cos(ϕ)+cos(θ)sin(ϕ) cos(θ+ϕ)=cos(θ)cos(ϕ)−sin(θ)sin(ϕ)Thus, we have all of the ingredients to write a closed-form solution to L{tnsin(bt+c)} and L{tncos(bt+c)}. But I’ll leave that up to you if you so choose.
Alternative Forms
As I stated earlier, there are various ways to represent A(m). Algebraically, I think these are the most straightforward.
A(m)=12(im+(−i)m)=12(1−(−1)m)imAnother alternative is to get rid of the summations altogether. We can do this as follows
L{tnsin(bt)}=n!(s2+b2)n+1⋅(s+ib)n+1−(s−ib)n+12i L{tncos(bt)}=n!(s2+b2)n+1⋅(s+ib)n+1+(s−ib)n+12Notice that all terms will be real because the imaginary terms always cancel out.